The Impact of RMB Internationalization on Total Factor Productivity in China: A Study Based on Provincial and Municipal Level - Xu, Hongrui (Transactions on Economics, Business and Management Research, 2024)
In order to explore the impact of RMB internalization on China’s provincial and municipal TFP, this paper divides the sample into eastern, central and western regions based on the annual data from 2011 to 2022 at the macro level of China’s provincial and municipal levels, and takes 2015 as the time segmentation point. Using the fixed effect and PVAR model, this paper analyses the influence of RMB internationalization on TFP in different periods and regions and its dynamic characteristics. It is found that the degree of internationalization of RMB generally shows an upward trend of fluctuation, and the fluctuation of the degree of internationalization of RMB has a significant impact on the TFP of the eastern and central regions, but the impact on the western region is not obvious. From a regional perspective, RMB internationalization has a positive impact on TFP in the eastern and western regions, and the eastern region has the largest impact, but the impact on the central region is not significant. From the perspective of time, whether from overall or region perspective, the impact of RMB internationalization on TFP of provinces and cities in China mainly emerged gradually after 2015. Therefore, in the increasingly complex internal and external environment, it is necessary to promote the deepening of RMB internationalization timely and effectively, and strengthen the positive impact of RMB internationalization on China’s TFP.